2021
DOI: 10.1002/anbr.202000116
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Detects the Difference in Cancer Cells of Different Neoplastic Aggressiveness via Machine Learning

Abstract: A novel method based on atomic force microscopy (AFM) working in Ringing mode (RM) to distinguish between two similar human colon epithelial cancer cell lines that exhibit different degrees of neoplastic aggressiveness is reported on. The classification accuracy in identifying the cell line based on the images of a single cell can be as high as 94% (the area under the receiver operating characteristic [ROC] curve is 0.99). Comparing the accuracy using the RM and the regular imaging channels, it is seen that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…30 Furthermore, the use of a novel AFM imaging mode, named Ringing mode, allowed to separate two similar cell lines of human colorectal epithelial cancer of different aggressiveness based on the use of images of the cell surface. 31 The brush model was suggested to find the effective Young's modulus of the cell body, which is covered with the PB layer, through the analysis of the force curves collected in AFM indentation experiments. The model takes into account the presence of the non-Hertzian behavior of the PB layer.…”
Section: Introductionmentioning
confidence: 99%
“…30 Furthermore, the use of a novel AFM imaging mode, named Ringing mode, allowed to separate two similar cell lines of human colorectal epithelial cancer of different aggressiveness based on the use of images of the cell surface. 31 The brush model was suggested to find the effective Young's modulus of the cell body, which is covered with the PB layer, through the analysis of the force curves collected in AFM indentation experiments. The model takes into account the presence of the non-Hertzian behavior of the PB layer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 65 ] It has been applied in studies of ocular surfaces and tissue engineering in the visual science field [ 66 ] and even in cancer research. It has already been used for characterization of breast tissue tissues, [ 67 ] bladder cancer detection, [ 68 ] differentiation of human colon cancer epithelial cells with varying neoplastic aggressiveness, [ 69 ] evaluation of cell adhesiveness and elasticity, [ 70 ] studying mechanical properties of cancerous cells, [ 71,72 ] and measurement of viscoelasticity of cancer cells in comparison with healthy cells. [ 73,74 ] Imaging in fluids, including physiological buffers, and compiling dynamic data are possible tasks using AFM.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…38 Furthermore, it has been demonstrated that the cell surface can be substantially changed as a result of genetic alterations. 39…”
Section: Introductionmentioning
confidence: 99%
“…38 Furthermore, it has been demonstrated that the cell surface can be substantially changed as a result of genetic alterations. 39 In this work, we use the AFM technique to measure the physical properties of NMR and mouse fibroblasts in response to malignant transformations induced by LT oncoproteins and the Ras oncogene. Indentation force curves were collected with AFM.…”
Section: Introductionmentioning
confidence: 99%